Quantitative proteomic profiling of bovine follicular fluid during follicle development - Ferrazza, Rodrigo de Andrade [UNESP]; Mogollon Garcia, Henry David [UNESP]; Santos Schmidt, Elizabeth Moreira dos [UNESP]; Carmichael, Monika Mihm; Souza, Fabiana Ferreira de [UNESP]; Burchmore, Richard; Sartori, Roberto; Eckersall, Peter David; Pinheiro Ferreira, Joao Carlos [UNESP] (Oxford Univ Press Inc, 2017)
Bovine follicular fluid (FF) constitutes the microenvironment of follicles and includes various biologically active proteins. We performed a study involving 18 healthy nonlactating Holstein cows to determine the protein expression profile of FF at key stages of follicular development. Follicles were individually aspirated in vivo at predeviation (F1 similar to 7.0 mm), deviation (F1 similar to 8.5 mm), postdeviation (F1 similar to 12.0 mm), and preovulatory stages of follicle development, which were confirmed by measurement of follicular estradiol and progesterone concentrations. The FFs from nine cows were selected for proteomic analysis. After albumin depletion, triplicates of pooled FF were reduced, alkylated, and digested with trypsin. The resulting peptides were labeled with TMTsixplex and quantified using liquid chromatography-mass spectrometry/mass spectrometry. A total of 143 proteins were identified and assigned to a variety of biological processes, including response to stimulus and metabolic processes. Twenty-two differentially (P < 0.05) expressed proteins were found between stages indicating intrafollicular changes over development, with expected deviation time critical to modulate the protein expression. For instance, high concentrations of follistatin, inhibin, serglycin, spondin-1, fibrinogen, and anti-testosterone antibody were found during early stages of follicular development. In contrast, apolipoprotein H, alpha-2-macroglobulin, plasminogen, antithrombin-III, and immunoglobulins were increased after deviation. Among the differentially abundant proteins, 19 were found to be associated with steroidogenesis. Pathway analysis identified proteins that were mainly associated with the acute phase response signaling, coagulation system, complement system, liver/retinoid X receptor activation, and biosynthesis of nitric oxide and reactive oxygen. The differentially expressed proteins provide insights into the size-dependent protein changes in the ovarian follicle microenvironment that could influence follicular function. Summary Sentence The protein dynamic changes in ovarian follicle microenvironment during the follicle development are critical for follicular maturation and influence follicular function in cows.
Keywords: folliculogenesis; proteomic; steroid hormone; mass spectrometry; Holstein cow